Protein from renewable resources: mycoprotein production from agricultural residues - Upcraft, Thomas; Tu, Wei-Chien; Johnson, Rob; Finnigan, Tim; Van Hung, Nguyen; Hallett, Jason; Guo, Miao (Royal Society of Chemistry, 2021)
Protein fermentation, intended for human consumption, from agricultural residues has been shown to be a potential viable process from a technical, economic and sustainability perspective.